Five-Year Data of Clinical Characteristics and Laboratory Findings of Hospitalized Hemophilic Patients in Dr. Hasan Sadikin General Hospital - Dina Marlina; Lelani Reniarti; Fifi Veronica (Althea Medical Journal, 2016)
Background: Hemophilia A has the highest incidence, more than 80% of 172.323 cases worldwide in 2012. It is stated that clinical characteristics of hemophilia A is worse than others, so it is required to prove and to know further about the clinical characteristics and severity likelihood in all hemophilic patients in order to prevent re-bleeding and re-injury and also for a better medical response.Methods: A retrospective cross-sectional study was carried out to 43 medical records of hospitalized hemophilic patients from 2009 to 2013 in Dr Hasan Sadikin General Hospital. The inclusion criteria were a complete patient identity (name, age, sex), written chief complaint, complete physical examination (bleeding, edema, hematoma, hemarthrosis, anemic symptoms) and laboratory test results (factor level, hemoglobin, hematocrit, platelet and Activated Partial Thromboplastin Time). The data was collected from August‒October 2014, analyzed and presented using frequency distribution.Results: Most of the patients were 5-10 years old, male and had hemophilia A. The most common complaint was external bleeding, followed by edema. From 43 patients, 38 (88%) cases were classified as severe factor deficiency, had mild to severe anemia, however the platelet count in most of the cases was in normal value. About 91% cases had prolonged Activated Partial Thromboplastin Time in moderate to severe level.Conclusions: Similar with other studies worldwide, most of the hospitalized hemophilic patients have hemophilia A. Most of the patents has moderate to severe bleeding with laboratory test result between moderate to severe level as well. [AMJ.2016;3(4):605–9]